Twin Peaks, ou l’exploration de l’espace américain - Zachary Baqué (Anglophonia)
Most studies of David Lynch's work tend to include Twin Peaks (1990-1991) in their interpretation, thus forgetting that the auteur theory cannot easily operate when TV series are analyzed, insofar as they are less the products of a single person than the point at which various interests intersect. According to the director, one of the reasons for the success of the series is that it can he labeled as "very American." The aim of this article is to show that there are three major ways of representing the American territory onscreen, which all have a specific aesthetic function (poetic, realistic and metafilmic). Thus American space is first understood as a semiotic entity, then as a human creation and finally as a crux in which pre-existing fictions converge to become myths. Twin Peaks does not turn elements of Americana into fetishes, it simply underlines the fact that they are constructed or idealized.